2015
DOI: 10.5713/ajas.13.0627
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Genetic Parameters for Somatic Cell Scores of Holsteins Using Multi-trait Lactation Models in Korea

Abstract: The study was conducted to analyze the genetic parameters of somatic cell score (SCS) of Holstein cows, which is an important indicator to udder health. Test-day records of somatic cell counts (SCC) of 305-day lactation design from first to fifth lactations were collected on Holsteins in Korea during 2000 to 2012. Records of animals within 18 to 42 months, 30 to 54 months, 42 to 66 months, 54 to 78 months, and 66 to 90 months of age at the first, second, third, fourth and fifth parities were analyzed, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…The heritabilities seem to be mostly in the low magni tudes, indicating greater environmental interferences in the manifestation of the trait. Such heritabilities are consistent with recent studies in Brazil [ 19 ] and other countries, such as South Korea [ 20 ], Iran [ 21 ], and Germany [ 22 ]. Although these heritabilities are still low, the parameter can be improved not only for SCS, but also indirectly for the resistance to mastitis.…”
Section: Discussionsupporting
confidence: 92%
“…The heritabilities seem to be mostly in the low magni tudes, indicating greater environmental interferences in the manifestation of the trait. Such heritabilities are consistent with recent studies in Brazil [ 19 ] and other countries, such as South Korea [ 20 ], Iran [ 21 ], and Germany [ 22 ]. Although these heritabilities are still low, the parameter can be improved not only for SCS, but also indirectly for the resistance to mastitis.…”
Section: Discussionsupporting
confidence: 92%
“…Lower SCS was found at peak milk yield, then increased for the remainder of the lactation which is in close agreement with previous studies [8,11]. The average level of SCS increased with increasing parity which agrees with previous studies [11][12][13][14]. An increase in the SCS with increasing parity can be attributed to the fact that older cows have more opportunity for exposure to mastitis-causing pathogens [15][16][17].…”
Section: Discussionsupporting
confidence: 90%
“…Over the years, most dairy breeding goals aim at increasing the milk production by high-strength artificial selection while ignored health traits such as mastitis resistance. A higher yielding cow results in a higher risk of mastitis, which would lead to an involuntary and premature culling of milking cows for defective udder characteristics and decreased milk yield [ 13 , 14 ]. In the breeding of cattle, dairy breeds were less resistant to mastitis than dual-purpose breeds [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since it is difficult to measure the mastitis phenotype using a direct index, milk SCS has been most widely used as an index to evaluate mastitis [ 13 ]. Milk SCS is a logarithmic transformation of the milk somatic cell count (SCC) to achieve normality of distribution in statistics which has positive correlation with clinical mastitis [ 14 17 ]. In the present study, two single nucleotide polymorphisms sites of α1 - AT gene were found in Chinese Holstein cows and their relationships with SCS were also studied; the results may provide a theoretical basis for marker-assisted selection of mastitis resistance in Chinese Holstein cows.…”
Section: Introductionmentioning
confidence: 99%